Body Composition Characteristics of Community-Dwelling Older Adults With Dynapenia - Jung, Hungu; Tanaka, Shigeharu; Tanaka, Ryo (Frontiers in Nutrition, 2022)
This study aimed to determine the differences in muscle mass and fat mass of the arm and leg among dynapenic, sarcopenic, pre-sarcopenic, and normal older adults. The percent body fat, lean body mass, and skeletal mass index were measured with bioelectrical impedance analysis. Muscle function was evaluated using grip strength and walking speed. Participants were classified into four sarcopenia categories. Sarcopenia was defined as the presence of both low muscle mass and low muscle function. Pre-sarcopenia was defined as low muscle mass with normal muscle function. Dynapenia was defined as low muscle function with normal muscle mass. Normal was defined as normal muscle mass and function. Multivariate analyses of variance were performed separately for women and men to test the main effect of sarcopenia category on body composition. Among the 376 enrolled participants, 270 were women and 86 were men. In older women, the dynapenia group had significantly less muscle mass in the leg than the normal group. In older men, the sarcopenia group showed a higher percent body fat in the arm and leg than the normal group. These results suggest that different strategies are needed for preventing dynapenia and sarcopenia in females and males.